2021
DOI: 10.1002/adom.202001903
|View full text |Cite
|
Sign up to set email alerts
|

Dual Laser Study of Non‐Degenerate Two Wavelength Upconversion Demonstrated in Sensitizer‐Free NaYF4:Pr Nanoparticles

Abstract: Understanding the upconversion pathways of a rare‐earth dopant is crucial to furthering the use of that material, either toward applications in imaging or elsewhere. This work outlines a new analysis approach that consists of using two synchronized widely‐tunable laser sources to explore the properties of upconverting materials. By examining sensitizer‐free rare‐earth nanoparticles based on a matrix of hexagonal sodium yttrium tetrafluoride (β‐NaYF4) doped with praseodymium but no ytterbium sensitizer, a “non‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…44 Specifically, the strongest blue emission at 492 nm is attributed to the 3 P 0 → 3 H 4 transition and the red emission at 614 nm is ascribed to the 3 P 0 → 3 H 6 transition. 45,46 As exhibited in the CIE diagram and digital photos in Fig. 5b, multi-color emissions can be easily realized by X-rays irradiating the β-NaYF 4 :RE 3+ samples.…”
Section: Resultsmentioning
confidence: 99%
“…44 Specifically, the strongest blue emission at 492 nm is attributed to the 3 P 0 → 3 H 4 transition and the red emission at 614 nm is ascribed to the 3 P 0 → 3 H 6 transition. 45,46 As exhibited in the CIE diagram and digital photos in Fig. 5b, multi-color emissions can be easily realized by X-rays irradiating the β-NaYF 4 :RE 3+ samples.…”
Section: Resultsmentioning
confidence: 99%
“…28 Pr 3+ doped materials were produced a nondegenerate two wavelength upconversion excitation pathway of 1020 and 850 nm leading to visible light emission. 29 In our previous work focused on the plasma characterization during the GGG crystal ablation, we found a strong dependence of the plasma properties on the partial oxygen pressure. Depending on the oxygen pressure, the ratio of emission from [Gd] and [Ga] in plasma varied from 3:5 to 1:1 and GGP crystal could be fabricated on the perovskite substrate.…”
Section: Introductionmentioning
confidence: 90%
“…Many excellent works on TSTF UCNPs have been reported [37][38][39][40][41] . For example, Chen et al 37 demonstrated that enhanced UCL intensity in NaYF 4 :1%Er nanoparticles were realized by 790 & 1520 nm excitation.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] For example, Chen et al37 demonstrated that enhanced UCL intensity in NaYF 4 :1%Er nanoparticles was achieved by 790 & 1520 nm excitation. Li et al 38 demonstrated that enhanced red emission in Gd 2 MoO 6 :Er/Yb nanoparticles co-doped WO 6 6À and La 3+ was achieved by 980 & 1550 nm excitation.…”
mentioning
confidence: 99%